Engendering democracy - Phillips, Anne 1950- (Pennsylvania State University Press, 1991)
Democracy is the central political issue of our age, yet debates over its nature and goals rarely engage with feminist concerns. Now that women have the right to vote, they are thought to present no special problems of their own. But despite the seemingly gender-neutral categories of individual or citizen, democratic theory and practice continues to privilege the male. This book reconsiders dominant strands in democratic thinking - focusing on liberal democracy, participatory democracy, and twentieth century versions of civic republicanism - and approaches these from a feminist perspective. Anne Phillips explores the under-representation of women in politics, the crucial relationship between public and private spheres, and the lessons of the contemporary women's movement as an experience in participatory democracy.